Prolonged response to vismodegib in a patient with systemic medulloblastoma metastases - Climans, Seth A (BMJ Case Rep, 2020)
Some patients with metastatic medulloblastoma can be successfully treated with targeted therapy. We report the case of a 42-year-old woman who was diagnosed with sonic hedgehog (SHH)-subgroup medulloblastoma. She was treated with surgery, radiation and chemotherapy. She then developed bone pain. A positron emission tomography (PET) scan confirmed widespread bone metastases from her medulloblastoma. She was started on vismodegib, an oral smoothened inhibitor that targets her tumour type. Her bone pain resolved. A repeat PET scan showed resolution of almost all metastases. Fourteen months after starting vismodegib, her disease recurred and she was transitioned to temozolomide chemotherapy. We document an important case of prolonged response to vismodegib in a patient with systemic SHH-subgroup medulloblastoma metastases.